Comparison of Decompressive Craniectomy and Multi-Dural Stabs with Decompressive Craniectomy and Open-Dural Flap Method, in the Treatment of Acute Subdural Hematomas - Adil Aziz Khan, Soban Sarwar Gondal, Muhammad Mujahid Sharif, Muhammad Ali Tassaduq (Journal of Rawalpindi Medical College, 2017)
Background: To compare the functional outcome between decompressive craniectomy and multi-dural stabs, with decompressive craniectomy and open-dural flap, in the removal of acute subdural hematomas . Methods : In this randomized controlled trial, 64 patients, with acute sub-dural hematomas were included. Patients were divided into two groups on the basis of lottery method. All patients gave informed written consent. In group A, all patients were operated upon by multi-dural stab technique and in group B, patients were operated upon by open-dural flap technique. The objective degree of recovery in the patients treated by both craniectomy techniques was assessed by Glasgow Outcome Score (GOS), having maximum of 5 and minimum of 1 score. Favourable outcome was at points 4-5 and Un-favourable at 1-3 points, at 2 weeks. GOS attached as annexure A. Favourable outcome was assessed at 2 weeks according to GOS. Results : The mean age in group-A and group-B was 59.09 ± 9.39 years and 59.56 ± 9.98 years. Males constituted the main in both groups. Mean GOS in group A and in group B, was 3.06 ± 1.24 and 2.69 ± 0.82 respectively. Statistically mean GOS was same in this study groups, p-value 0.159, > 0.05. There were 37.5% patients in group A and 9.4% patients in group B who had favourable results, while in group A and group B, 62.5% and 90.60% patients had unfavourable results. Favourable results were statistically more in group A as compared to group B, p-value =0.008. Conclusion: Treatment of acute subdural hematoma by decompressive craniectomy with multi dural stabs technique has more favourable results (using GOS) than decompressive craniectomy with open-dural flap technique.